AZAB DALAM ESKATOLOGI IBN ‘ARABI - Iskandar Arnel (An-Nida', 2014)
The present article discusses Ibn ‘Arabî’s eschatological perspective on the notion of punishment (‘adzâb) in the Hell Fire. It focuses on his idea on the meanings of ‘adzâb and on how it effects the people of Hell Fire. Utilizing the Futûhât, the article finds that the Syaykh perceives it as Divine Mercy (rahma’) towards the sinners in order to purify them from all the sins they had committed in the worldly life. He also states that upon its completion, the ‘adzâb will then turn into ‘adzûba’ (sweet, pleasant) in two ways: the people of Hell Fire from among the Muslim believers (muwahhidûn) will move to Heaven, whereas those of the non-believers (kuffâr), hypocrites (munâfiqûn) and polytheists (musyrikûn) will remain in Hell forever yet without suffering the torment anymore